Christus in onze angst: over een onderbelicht obstakel voor een Europese theologie van de migratie - De Maeseneer, Yves (Tijdschrift voor theologie, 2017)
The ever growing theological literature on migration fails to address the aspect of ‘fear’. Taking its lead from S. Snyder, this essay attempts to take the fear among the European population seriously and formulate a theological response to it. The main question of this essay consists in the impact of fear upon our identity and how this affects our relationship to those seeking safety among us. From this tension between identity and solidarity, we try to deal with our fears in such a way that it does not hinder us from inhabiting the world as ‘our common home’. How can we get past the polarization (us vs. them) to find a new communality? What is at stake here, is a fundamental transition from an ‘ecology of fear’ to an ‘ecology of faith’ – categories that point to different ways of inhabiting our world. Scripture narratively mirrors who we are and helps us to critically transform the current social imaginary with regard to refugees and migration (Ezra/Nehemiah, Ruth, Jesus and the Syrophoenician woman). Inspired by Ephrem the Syrian’s suggestion that Jesus entered our fears and took them upon Himself to deliver us from them, this essay does not merely see Christ’s presence in those asylum seekers who are excluded and intimidated in our current culture of fear but mutatis mutandis, in the xenophobic fears among the autochthonous population. This Christological groundwork allows for a fundamental solidarity at the level of our fears, of the kind rabbi Jonathan Sacks referred to in his appeal to take the opposite course in our polarized context: ‘speaking our fears, listening to the fears of others, and in that sharing of vulnerabilities discovering a genesis of hope’. Hospitality and fear are no longer each other’s opposites; welcoming one another’s fears is now a source of new solidarity. In our pursuit of this kind of sharing and mutual recognition of fears, the first step could be praying of so-called ‘prayers of fear’ together. We use Psalm 27 to illustrate the dynamics of turning fear from an obstacle into a transit, a way of finding a locus for our fears within a redemptive surroundings, on the basis of a vicarious trust.